Differential impact of 5-lipoxygenase-activating protein antagonists on the biosynthesis of leukotrienes and of specialized pro-resolving mediators - Dahlke, Philipp; Peltner, Lukas K.; Jordan, Paul M.; Werz, Oliver (Frontiers in Pharmacology, 2023)
Lipoxygenases (LOX) transform arachidonic acid (AA, C20:4) and docosahexaenoic acid (DHA, C22:6) into bioactive lipid mediators (LM) that comprise pro-inflammatory leukotrienes (LT) but also the specialized pro-resolving mediators (SPM) that promote inflammation resolution and tissue regeneration. The 5-LOX-activating protein (FLAP) is known to provide AA as substrate to 5-LOX for generating LT, such as LTB4, a potent chemoattractant and activator of phagocytes. Notably, 5-LOX is also involved in the biosynthesis of certain SPM, namely of lipoxins and D-resolvins, implying a role of FLAP in SPM formation. FLAP antagonists have been intensively developed as LT biosynthesis inhibitors but how they impact SPM formation is a matter of debate. Here, we show that FLAP antagonism suppresses conversion of AA by 5-LOX to LT and lipoxins, while the conversion of DHA to SPM is unaffected. Screening of multiple prominent FLAP antagonists for their effects on LM formation in human M1-and M2-monocyte-derived macrophages (MDM) using comprehensive LM profiling showed that all nine compounds reduced production of 5-LOX-derived LTs but elevated formation of SPM from DHA, e.g., resolvin D5. Some FLAP antagonists, especially some that contain an indole or benzimidazole moiety, even elicited SPM formation in resting M2-MDM. Intriguingly, in coincubations of human neutrophils and platelets that produce substantial AA-derived lipoxin and DHA-derived RvD5, FLAP antagonism abolished lipoxin formation, but resolvin D5 levels remained unaffected. Conclusively, antagonism of FLAP suppresses conversion of AA by 5-LOX to LTs and lipoxins but not the conversion of DHA by 5-LOX to SPM, which should be taken into account for the development of such compounds as anti-inflammatory drugs.